The First International seen from the periphery: The Portuguese case (1871-1876) - Lázaro, J. (Labour History Review, 2023)
This article discusses the influence the Spanish workers’ movement had in the creation of the Portuguese section of the First International (the International Working Men’s Association) and the political struggles faced by the First International in Portugal. From 1871 until 1876, a battle for the periphery became evident in Portugal, as conflicts grew between the London-based General Council (Marxists) and anarchists (Bakuninists) based in Switzerland, Italy, and Spain. The emergence of the Portuguese section opened the way for a new political arena for internal clashes of the First International as both factions sought to control the Portuguese labour movement. The influence on Portuguese socialism by the General Council’s supporters (mainly Engels, Marx, and Paul Lafargue) was clear, however. On the other hand, the anarchist International Alliance of Socialist Democracy persevered with its contacts with the Portuguese. Both factions were, above all, interested in the International’s potential to act as a transnational organization and to challenge for influence in the Portuguese section of the International.